Realization of diamagnetic levitation of column-shaped graphite - Keisuke IIDA (The Japan Society of Mechanical Engineers, 2015)
The completely passive levitation of a column-shaped graphite object is achieved. Graphite is a typical diamagnetic material. Diamagnetic materials have a property of generating repulsive force in magnetic field. Most diamagnetic levitation systems use high-oriented pyrolytic graphite (PG) sheets because sufficient force for levitation is easily obtained. In contrast, column-shaped graphites are proposed as the target of levitation in this work. Experimental apparatus for diamagnetic levitation is fabricated. The apparatus uses a two-dimensional Halbach array made of cubic neodymium magnets. The magnetic fields in the apparatus are analyzed numerically and experimentally. It is shown that the stable diamagnetic levitation of a column-shaped graphite can be achieved. The floator is fabricated by combining the pencil leads made from graphite. Then the diamagnetic forces acting on the floator are measured. In addition, the effects of anisotropy of graphite on the levitation characteristics are discussed.